A política de comunicação televisiva no Brasil e na Espanha - Silva, Luciene Pazinato da (2016)
The aim of the current thesis is to understand the role of the television into the social and political context in Brazil and in Spain, as well as the constitutive process of public information broadcasted on the public TV channels about the social movements, considering the framing (or background) given by the news channels in relation to the visibility of the social actors, and of the politicians during the manifestations. In order to do so, a comparative analysis of the public communication between Spain and Brazil was conducted, and the research aim was on the press coverage performed by the following TV news programs: Telediario 2, Canal La 1, Spanish Public TV – RTVE, about 15-M Movement, “Indignados” (“The Outraged”), which took place at the main squares of the Capitals of the Autonomous Communities of Spain, in the months of May and June of 2011, and the news broadcast of Repórter Brasil, of the Brazilian public TV, TV Brasil, during the manifestations that took place on the main streets, avenues and squares of the capitals in Brazil during the four weeks of June 2013. We considered the contribution given by the contemporaneous theoreticians of the political communication, as well as the social movements themselves, and the discussions about public TV. The methodology of media framing was used for the empirical study, and it resulted in the analyses of the matters broadcasted, and in the predominance of the limited visibility given to the social movements